Organic–inorganic composite micro-granules by evaporation induced assembly: role of trapped water in structural evolution1. Issue 29 (2nd April 2015) - Sen, D.; Lakhotiya, H.; Das, Avik; Bahadur, J.; Mazumder, S.; Basak, C. B.
<x xml:space="preserve">Abstract</x> Nano-structured composite micro-granules are promising candidates for many technological and medical applications.